Doskonalenie kompetencji muzycznych studentów edukacji wczesnoszkolnej podczas zajęć terenowych w szkole - Kisiel, Mirosław (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The paper is written in order to present the results of research showing students and tutors’ opinions on possibilities and effects of improving students’ musical and pedagogical competences in early school education. Information on the implementation of the educational project titled „Practice Makes Perfect!” is also included in the paper.
Keywords: early school education; music competence; school practice; student